2018
DOI: 10.4103/ortho.ijortho_598_16
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Transosseous Repair for both Proximal and Distal Components of Peripheral Triangular Fibrocartilage Complex Tear

Abstract: Background:Tears of the triangular fibrocartilage complex (TFCC) can result in instability of the distal radioulnar joint (DRUJ) and ulnar-sided wrist pain. This study evaluates clinical results of arthroscopic transosseous repair for both proximal and distal components of TFCC tear with DRUJ instability.Materials and Methods:Ten patients who underwent both proximal component and distal component of TFCC repair were retrospectively reviewed. The proximal component of TFCC was repaired through arthroscopic one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Radial and ulnar deviation, unsurprisingly, did not change following ALSR as the proximal components of TFCC are not involved in this axis of wrist motion (Nakamura et al., 2018). Our findings are consistent with the previously reported outcomes for arthroscopic TFCC repair, which showed that patient-reported outcomes, pain, grip strength and range of pronation–supination all invariably improve following surgery (Atzei et al., 2015; Jegal et al., 2016; Park and Park, 2018; Shinohara et al., 2013). Interestingly, while all of our patients had a negative ballottement test postoperatively, not all patients have had successful restoration of stability in the series published using isometric point techniques.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Radial and ulnar deviation, unsurprisingly, did not change following ALSR as the proximal components of TFCC are not involved in this axis of wrist motion (Nakamura et al., 2018). Our findings are consistent with the previously reported outcomes for arthroscopic TFCC repair, which showed that patient-reported outcomes, pain, grip strength and range of pronation–supination all invariably improve following surgery (Atzei et al., 2015; Jegal et al., 2016; Park and Park, 2018; Shinohara et al., 2013). Interestingly, while all of our patients had a negative ballottement test postoperatively, not all patients have had successful restoration of stability in the series published using isometric point techniques.…”
Section: Discussionsupporting
confidence: 93%
“…There are limitations to this study. It is of retrospective design with a relatively small number of participants, although comparable with the existing literature (Atzei et al., 2015; Jegal et al., 2016; Nakamura et al., 2011; Park and Park, 2018; Shinohara et al., 2013). It is a single series study, without comparison with other methods of foveal repair.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Similar to non-surgical treatment, previous authors have recommended that the forearm should also be immobilized with a LAC in supination following TFCC foveal repair. 7,8,15 However, others have reported favourable outcomes when the forearm was immobilized with a LAC in the neutral position after this procedure. As with differences in the position of the forearm with a LAC, the recommended duration of immobilization in a cast also varies from four to six weeks.…”
Section: Discussionmentioning
confidence: 99%
“…arthroscopic surgery, several authors have reported favourable outcomes of arthroscopy-assisted repair in the treatment of foveal tear. [6][7][8][9][10][11] Rotation of the forearm is not a purely rotational movement but includes sliding as the curvature of the sigmoid notch of the radius is twice as large as that of the ulnar head. 2,12 The DRUJ is thus inherently unstable.…”
mentioning
confidence: 99%